2016 IEEE Radar Conference (RadarConf) 2016
DOI: 10.1109/radar.2016.7485251
|View full text |Cite
|
Sign up to set email alerts
|

Non-fluctuating target detection in fluctuating K-distributed interference and noise

Abstract: Abstract-This paper deals with the problem of non-fluctuating target detection in the presence of a mixture of heavy tailed K-distributed clutter and independent noise. Prior papers have derived generalized likelihood ratio tests (GLRT) for this problem as well as approximations of the GLRT. These results show the required optimum processing and its vastly different efficiency as compared to similar results derived under standard Gaussian assumptions. In this study we examine the detection performance of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…radar returns, and where and stand for the target signature and amplitude, respectively. In [15], we showed that, in contrast to what is commonly admitted, thermal Gaussian noise cannot be ignored, even if clutter to noise ratio is high. Indeed, it was shown that, for heavy-tailed distributions, the detection performance is in fact dominated by a single observation within the i.i.d.…”
Section: Introduction and Problem Statementmentioning
confidence: 82%
See 4 more Smart Citations
“…radar returns, and where and stand for the target signature and amplitude, respectively. In [15], we showed that, in contrast to what is commonly admitted, thermal Gaussian noise cannot be ignored, even if clutter to noise ratio is high. Indeed, it was shown that, for heavy-tailed distributions, the detection performance is in fact dominated by a single observation within the i.i.d.…”
Section: Introduction and Problem Statementmentioning
confidence: 82%
“…The normalized matched filter (actually the non coherent integration of the NMF for a single snapshot) is given by (8) Finally, in [15], we discovered that the test statistic in (5) is mostly influenced by the term corresponding to the minimal value of . Let be this snapshot and let us consider the hypothetical test statistic (9) We first study the behavior of the detectors in (5)-(9) under .…”
Section: Robustness To Each Type Of Noisementioning
confidence: 92%
See 3 more Smart Citations